2010
DOI: 10.1021/pr1004828
|View full text |Cite
|
Sign up to set email alerts
|

2D-DiGE Analysis of the Human Endometrial Secretome Reveals Differences between Receptive and Nonreceptive States in Fertile and Infertile Women

Abstract: Endometrial secretions in the uterine cavity contain mediators important for endometrial receptivity and embryo implantation. Unbiased analysis of uterine fluid from a receptive versus nonreceptive time of the menstrual cycle and in fertile and infertile women will provide new insights into uterine receptivity. We hypothesized that proteomic analysis of human uterine lavages would identify proteins important for the establishment of pregnancy in humans. Lavages collected from fertile (n = 7) and infertile (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
111
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 128 publications
(120 citation statements)
references
References 51 publications
(102 reference statements)
6
111
0
3
Order By: Relevance
“…A comparison of protein abundances between the fertile and infer tile women revealed that several proteins were present at altered levels depending on cycle stage or fertility status (21). Nevertheless, most of the microvilli remained comparable in terms of size and number in both groups despite an irregular appearance in the RIF group (Figure 2a).…”
Section: Discussionmentioning
confidence: 97%
“…A comparison of protein abundances between the fertile and infer tile women revealed that several proteins were present at altered levels depending on cycle stage or fertility status (21). Nevertheless, most of the microvilli remained comparable in terms of size and number in both groups despite an irregular appearance in the RIF group (Figure 2a).…”
Section: Discussionmentioning
confidence: 97%
“…Accumulated evidence suggests that the EF serves as the 'uterine milk' (Burton et al, 2007;Khalil et al, 2009) that nurtures the embryo not only during implantation but beyond (Godfrey and Barker, 2001;Kennedy et al, 2007). The EF contains a variety of molecules, including glycodelin (van der Gaast et al, 2009), cytokines (Boomsma et al, 2009;Simón et al, 1996), lipids and proteins (Domínguez et al, 2009;Hannan et al, 2010), but their impacts on embryo physiology and the putative developmental origins of adult diseases are unknown (Barker, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Hannan et al studied the endometrial secretome of seven fertile women during both the mid-proliferative and mid-secretory phase and compared it with that of eight infertile women only during the mid-secretory phase. The comparison identified seven proteins that were significantly more highly expressed during the mid-secretory phase in the first group, whereas 18 spots showed differential expression (12 were increased and six were reduced) between the two groups of patients that subsequently needed to be further investigated concerning their functionality (120). Similarly, Scotchie et al identified 42 differentially expressed proteins in the uterine fluid in the pre-receptive and receptive state of the endometrium.…”
Section: Proteomics and Endometrial Receptivitymentioning
confidence: 99%